Antiviral therapy for COVID-2019 - Hanik Badriyah Hidayati, - (Faculty of Anaesthesia, AFMS, 2021)
The whole world is experiencing a global pandemic caused by Coronavirus disease 2019. As the pandemic progresses, there has been much research on antiviral drugs, such as hydroxychloroquin, chloroquine, remdesivir, lopinavir-ritonavir, favipiravir, oseltamivir, and umifenovir. Specific antiviral drugs proven to be effective against SARS-CoV-2 have not been found and approved for the medication of COVID-19. Currently, case detection, infection control, monitoring, prevention, and supportive care are the means focused on the treatment of COVID-19. A large scale research is currently underway to analyze safety and efficacy of antiviral drugs, while trials of the SAR-CoV-2 vaccine are rapidly expanding. This mini review briefly introduces the current antiviral therapy for COVID-19.